Correlation between Coping Strategies and Quality of Life among Myocardial Infarction Patients in Nepal - Panthee, Bimala; Kritpracha, Charuwan; Chinnawong, Tippamas (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2011)
Objective: To examine the correlation between coping strategies and quality of life (QoL) among patients with myocardial infarction (MI) Method: A descriptive correlational design was used to examine the relationship between coping strategies and QoL among 88 patients with MI who were older than 18 years, 2 months after the initial diagnosis of MI. QoL was assessed using the cardiac version of the Quality of Life Index. Coping strategy was assessed using Jalowiec Coping Scale. Problem-focused coping and emotion-focused coping were also compared in male and female patients.Results: Problem-focused coping was significantly positively associated with overall QoL (r = .41, p = <.01), particularly the health and functioning dimension (rs = .39, p = <.01) and socio-economic dimension (rs = .46, p = <.01) but not with psychological & spiritual and family dimension. Men used more problem-focused coping strategies than women. The problem-focused coping score was significantly different between men and women (t = 4.9, p <.05).Conclusion: The results revealed that patients who used more of problem-focused coping had better QoL than patients who used less problem-focused coping. Educating patients to enhance the use of appropriate coping strategies may be useful to promote the QoL of Nepalese patients with MI. Key words: Coping, quality of life, myocardial infarction